1965
DOI: 10.1139/v65-355
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects in the Nuclear Magnetic Resonance Spectra of Benzalmalononitriles

Abstract: The nuclear magnetic resonance spectra of a series of substituted benzaln~alo~lonitriles were examined in various solvents. The chemical shifts for the olefinic protons are susceptible t o large solvent effects which are interpreted as arising from association of a solvent molecule with the olefinic proton (acetone) or a site in its vicinity (benzene). With acetone this leads to a downfield shift from values observed in chloroform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…I t has been shown by Weinberger et al (40) that a similar intermolecular association occurs between acetone and this hydrogen. Extension of this argument to difunctional styrenes, with the postulate of an intrainolecular association of the ortho methoxyl and a resonating cis functional group, would lead to a bathochromic shift in the wavelength of CZ-methoxy derivatives which was the same as that in the protonation of-the aldehyde of 4-~nethoxycinnam-aldehyde (18).…”
Section: T a B L E X X I Ultraviolet Absorption Maxima O F Some Unsatmentioning
confidence: 81%
“…I t has been shown by Weinberger et al (40) that a similar intermolecular association occurs between acetone and this hydrogen. Extension of this argument to difunctional styrenes, with the postulate of an intrainolecular association of the ortho methoxyl and a resonating cis functional group, would lead to a bathochromic shift in the wavelength of CZ-methoxy derivatives which was the same as that in the protonation of-the aldehyde of 4-~nethoxycinnam-aldehyde (18).…”
Section: T a B L E X X I Ultraviolet Absorption Maxima O F Some Unsatmentioning
confidence: 81%
“…Indeed, in both cases, the protons were further downfield compared tod 6 -Acetone (vide infra); however, it was the fact that the shifts were near the extremes and in opposite directions that caught our interest. The reversal of downfield shift in the presence of aromatic solvents has been previously observed [26]. It has been hypothesized that this is due to the H-bonding ability of the benzylic protons.…”
Section: Nmr Spectra Chemical Shiftmentioning
confidence: 55%
“…The degree of solute-solvent interaction is increased for solvents such as DMSO and acetone, as they are hydrogen bond acceptors. Hydrogen bonds act to deshield the protons, shifting their resonance downfield [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of DMF, the methyl trans to the carbonyl can adopt this role, consistent with its experimental shift appearing upfield and the data point for these methyl hydrogens falling on the secondary line while the cis methyl hydrogens fall on the primary line. Overall, this complexation significantly lowers the chemical shifts in solution, as expected for protons over the face of an aromatic system . Similar effects for acidic CH groups in hydrogen‐bonding solvents do not show themselves, indicating that the effect of the local magnetic fields of aromatic systems are larger than effects associated with changes in electron density distribution associated with hydrogen bonds.…”
Section: Resultsmentioning
confidence: 74%
“…Some errors were observed that likely reflect issues associated with using implicit rather than (the much more computationally challenging to implement) explicit treatment of solvent . For example, for the TFE scaling factors, the scaled methylene hydrogen shifts for triethylamine were over 0.6 ppm upfield of the experimental shifts.…”
Section: Resultsmentioning
confidence: 99%